A child's Alaska - Murphy, Claire Rudolf; Mason, Charles, 1958- (Anchorage : Alaska Northwest Books, 1994)
Young readers will see images of the amazing landforms--glaciers, mountains, and sprawling tundra; glimpse the North Country's distinctive creatures--musk oxen, grizzly bears, whales; learn about other cultures--Russian, Eskimo, Athabascan, Tlingit; and relate to the stories of the lives of their young Alaskan peers in cities and in the "bush."
Includes bibliographical references and glossary.
School Library Journal
Booklist starred
5.6
3-6
Keywords: Alaska -- Juvenile literature; Alaska -- Pictorial works -- Juvenile literature; Alaska; Alaska